Back Cover: Brain co‐delivery of first‐line chemotherapy drug and epigenetic bromodomain inhibitor for multidimensional enhanced synergistic glioblastoma therapy (EXP2 4/2022). Issue 4 (31st August 2022) - Liu, Yanjie; Wang, Wendie; Zhang, Dongya; Sun, Yajing; Li, Fangzhou; Zheng, Meng; Lovejoy, David B.; Zou, Yan; Shi, Bingyang
Abstract : Yan Zou and co‐workers present a temozolomide and epigenetic bromodomain inhibitor co‐encapsulated biomimetic nanomedicine platform that achieves prolonged blood circulation time, excellent blood brain barrier (BBB) permeability, and multidimensional enhanced glioblastoma (GBM) synergistic chemoimmunotherapy in both primary and recurrent orthotopic mice models with significant extended survival rate and little side effects.